2011
DOI: 10.1310/tsr1805-509
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Approach to Activity After Stroke: It Takes a Community

Abstract: There are layers of interactions between individuals and multiple factors in their environments that influence participation. Low poststroke activity levels may be amenable to intervention. Further research should consider the following: (1) participation in activities through the lens of all levels of the socioecological model; (2) the impact of disability and aging-related stigma; (3) the results of ad hoc community navigation; and (4) the effects of restrictive health and disability policies on meaningful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…Ages of participants ranged from 22 to 100 years; this was unreported in a few studies (n=7) [53],[54],[72],[105],[106],[110],[114]. Time since stroke (n=41) [7],[52],[55][58],[63][65],[68][71],[74],[78][80],[83][85],[87][89],[91][95],[97],[99][104],[107],[108],[110],[116][118] ranged from under 2 weeks to 16 years. Disability since stroke (n=39) [7],[54][56],[58],[61],[63],[65],[67][69],[71],[76],[77],[79][83],[85],[89]–[92],[95],[96],[99],[100],[102][104],[106],[108][110],[115],[117][119] was very variable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ages of participants ranged from 22 to 100 years; this was unreported in a few studies (n=7) [53],[54],[72],[105],[106],[110],[114]. Time since stroke (n=41) [7],[52],[55][58],[63][65],[68][71],[74],[78][80],[83][85],[87][89],[91][95],[97],[99][104],[107],[108],[110],[116][118] ranged from under 2 weeks to 16 years. Disability since stroke (n=39) [7],[54][56],[58],[61],[63],[65],[67][69],[71],[76],[77],[79][83],[85],[89]–[92],[95],[96],[99],[100],[102][104],[106],[108][110],[115],[117][119] was very variable.…”
Section: Resultsmentioning
confidence: 99%
“…Co-morbidities were seldom mentioned (n=11) [53],[67],[73],[77],[80],[86],[90],[93],[99],[100],[112] nor were medications (n=3) [7],[77],[86]. Qualitative data gathering methods: interviews (n=63)[7],[52][74],[76][91],[94][102],[105],[107][119]; focus groups (n=4) [93],[103],[104],[106]; interviews and focus groups (n=2) [75],[92]; additional field notes (n=5) [69],[87],[88],[111],[118]; additional patient observation (n=1) [95]. Data analysis: a variety of qualitative methods were used, and all sought to identify common themes raised by participants (details are described in Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thematic analysis revealed that valued activities could be divided into the following categories: reengagement in valued activities in general (studies about outdoor and indoor activities); 22,25,26,32,33,3546,48,6064,6772 social and community reengagement (studies about social activities outside the home and in the community); 21,23,27, 28,34,47,50,52,55,58,73,74 mobility (studies about moving around as a meaningful activity) 29,51,53,54,56,57,59 and work. 24,49,65,66,7586 Some single remaining studies on activities such as eating, exercise or leisure …”
Section: Resultsmentioning
confidence: 99%
“…Carers have expressed concern about stroke survivors being injured or being unable to rise from the floor [2,14]. Discrepancies in understanding of risk between some stroke survivors and their spouses have also been noted [15]. The importance of self-identity and self-efficacy is frequently discussed in qualitative research exploring the experience of living with stroke [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%